The identification of helminths and coccidia from goats in two farms in Kuala Terengganu, Malaysia - Hisamuddin, Nur Hazirah; Hashim, Najat; Soffian, Sharmeen Nellisa; Raja Abdul Rahman, Raja Nur Rahifah Inani; Mohammad, Mardhiah; Md Isa, Muhammad Lokman; Mat Yusof, Afzan (Universiti Teknologi Malaysia, 2016)
Helminths and coccidia are major causative agents causing parasitic infections in livestock production. The present study aimed to determine the prevalence and intensity of gastrointestinal helminths and coccidia in goats in Terengganu, Malaysia. A total of 227 goats which consists of 107 adult goats and 120 young goats were selected randomly from two farms located in Terengganu, Malaysia. Sodium chloride flotation technique was used to identify helminths eggs and coccidia oocysts. The number of eggs per gram and faecal oocysts count were determined by using modified McMaster technique. Out of 227 goats, 221 goats were positive for gastrointestinal parasites giving the overall prevalence 97.36%. The highest prevalence was recorded for Eimeria (89%) followed by Strongyloides (46.3%), Strongyle (18.1%), Monezia (10.6%) and the lowest prevalence was recorded for Trichuris spp. (9.7%). Coccidia oocyst counts were significantly higher in young goats as compared to adult goats while the Strongyle and Strongyloides egg counts were significantly higher in adult goats compared to young goats (P<0.05). The findings of this study suggested that good management practices and proper hygiene management are important to combat the infection so that there will be no case of parasitic infection among goats in the near future in Terengganu.